Behavioral Analysis of Shopee Application Users at Stmik Borneo International using the Technology Acceptance Model (TAM) Method - Yuliani, Hery; Hadisaputro, Elvin Leander (Green Publisher Indonesia, 2022)
The development of information technology today has a very rapid growth. Businesses began to enter the virtual world market called e-commerce. Shopee is one of the developing e-commerce. Therefore, it is necessary to know how the acceptance of an application technology by the public is used. In this research, the Shopee application is used, which is an online shopping platform that focuses on mobile, making it easier for users to shop and sell using gadgets. The method in this study uses the Technology Acceptance Model (TAM) research method. The results of this study note that Perceived Ease of Use does not have a significant positive effect on Attitude Toward Using Perceived Usefulness has a significant positive effect on Attitude Toward Using with the level of relationship. It can be concluded that the Perceived Usefulness, Attitude Toward Using, and Intention to use factors have a significant effect on the use of the Shopee application. Meanwhile, the perceived ease of use has no effect on the Shopee application, so it is recommended to improve the quality of the ease of use of the Shopee application.